Lesbian Lacunae: Invisible Spaces in Dance Education - Mozingo, Karen A. (Journal of Dance Education, 2005)
Recent research about sexuality and dance has begun to address the needs of gay male dancers, yet the needs of lesbian dancers have remained mostly absent from scholarly discourse. Exploring the lesbian lacunae, or invisible spaces of dance education, reveals the personal, political, and pedagogical implications of their existence within the dance community. The experiences of lesbian dancers “on the fringe” combined with new approaches to acknowledging lesbian artists and perspectives within dance history suggest the need for re-envisioning lesbian invisibility as a “liminal presence” within dance. In addition, ways dance educators can reduce the effects of heterocentrism within their institutions and celebrate the contributions of lesbian artists and educators to the field are proposed. By reconfiguring the invisibility of lesbian dancers as a liminal presence, we make visible the borders and limits of the dance profession's notions of sexuality and gender, acceptance and equality, and thereby strengthen our potential for dancing beyond them.
Keywords: Bibliographie; Nettoyer

Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer